Welcome :: Homework Help and Answers :: Mathskey.com
Welcome to Mathskey.com Question & Answers Community. Ask any math/science homework question and receive answers from other members of the community.

13,333 questions

17,804 answers

1,438 comments

35,281 users

Algebra help please.?

+2 votes
please help the best you can.
solve for x

7. -12(k-3)=-5
9. -3x+(7x-4)=8
10. 2/3(6c-12)=-9
11. 2x+11=20x
13. -20+4x=2x+6
14. -9x+6+4x=-13+14x
15. -2(8-5x)=3(x+2)
19. 3/x+4=5/2x
asked Jan 2, 2013 in ALGEBRA 2 by homeworkhelp Mentor
reshown Jan 2, 2013 by bradely

12 Answers

+2 votes


7. -12(k-3)=-5

 Given equation  -12(k-3) =  -5

 divide  each side  by negtive 12

  -12 / -12 (k-3)  =  -5 /-12

  (k-3) = 5 / 12                                  ( -12 / -12 =1; -5 / -12 = 5 / 12)

  Add 3 to each side

  k-3+3 = 5 / 12 +3

          k = 5+36 / 12

           k = 41 / 12

answered Jan 2, 2013 by ricky Pupil
reshown Jan 2, 2013 by bradely
+1 vote

9. -3x+(7x-4)=8

Given equation  -3x + (7x -4) = 8

                             -3x + 7x -4    = 8

                                        4x - 4 = 8

     Add 4 to each side

                        4x - 4 + 4 = 8+4

                                     4x = 12

  Divide each side by  4

                                     4x / 4 =12 / 4                 ( 12 / 4 = 3)

                                              x = 3              

answered Jan 2, 2013 by ricky Pupil
+1 vote

10. 2/3(6c-12)=-9

 Given equation  2/3(6c-12)=-9

 multiply each side 3

                              3*2/3 (6c-12) = -9*3

                                  2 (6c -12)   = -27  

                                     12c - 24   = -27

  Add 24 to each side 

                             12c-24+24   = -27+24

                                           12c = -3

  Divide  each side  by  12

                                           12 c / 12 = -3 /12

                                                      c = -1 / 4

                                      

answered Jan 2, 2013 by ricky Pupil
+2 votes

11. 2x+11=20x

Given equation 2x+11=20x

Subtract 2x from each side

                          2x+11-2x = 20x-2x

                         11 + 2x-2x = 18x

                                        11 = 18x

Divide each side by 18

                                       11 / 18 = 18 x / 18

                                         11 / 18 = x

                                                  x = 11 / 18

               

answered Jan 2, 2013 by ricky Pupil
+1 vote

13. -20+4x=2x+6

Given solutions  -20+4x=2x+6

Subtract 2x from each side

        -20 + 4x -2x = 2x +6 -2x

             -20 + 2x = 6+2x -2x

              -20 +2x = 6

Add 20 to each side       

        -20  +2x +20 = 6+20

           2x-20+20 = 26

                      2x = 26

  Divide each side by  2

              2x / 2 = 26 / 2

                    x=13

answered Jan 2, 2013 by ricky Pupil
+1 vote

14. -9x+6+4x=-13+14x

Given solution -9x+6+4x=-13+14x

Add 9x to each side

    -9x +6+ 4x +9x = 13+14x+9x

       6 + 4x+9x-9x = 13+23x

                   6+4x = 13+23X

Subtract 4x from each side  

        6+4x -4x = 13+23x-4x

                   6 = 13+19x

   Subtract 13 from each side  

            6-13 = 19x+13-13

           -7  = 19x

  divide  each side  by 19

     -7 / 19 = 19x /19

          x = -7/19

      

        

answered Jan 2, 2013 by ricky Pupil

The solution is x  = 1.

+1 vote

 

15. -2(8-5x)=3(x+2)

Given solution  -2(8-5x)=3(x+2)

 -2*8 -5x(-2) = 3x+6

Product of two same signs is positive

-16+10x = 3x+6 

Subtract 3x from each side

-16 + 10x -3x = 3x+6-3x

-16 + 7x  = 6

Add 16 to each side

-16+7x+16 = 6+16

   7x = 22

Divide each side by 7

 7x /7 =22/7                 

     x = 22 / 7  

 

answered Jan 2, 2013 by ricky Pupil
+1 vote

19. 3/x+4=5/2x

Given equation 3/x+4=5/2x

 multiply each side x

 3x / x +4x = 5x / 2x

      3 + 4x =5 /2

Subtract 3 from each side  

 3+4x-3 =5/2 -3

        4x =5-6/2

       4x = -1 / 2

 divide  each side  by  4

    4x / 4 =-1/2*4

         x =-1/8

                 

answered Jan 2, 2013 by ricky Pupil
+1 vote
The equation is  -12(k-3) = -5

-12(k-3) = -5

Multiply each side by negative one.

-(-12(k-3)) = -(-5)

Product of  two same signs is positive.

12(k-3) = 5

Divide each side by 12.

12(k-3)/12 = 5/12

k-3 = 5/12

Add 3 to each side.

k-3+3 = 5/12+3

k = 5/12 + 3

k = (5+36)/12

k = 41/12.
answered Jan 2, 2013 by david Expert
+1 vote

. -12(k-3)=-5

 Given equation  -12(k-3) =  -5

 divide  each side  by - 12

  -12(k -3) / -12  =  -5 /-12

  (k-3) = 5 / 12                                  ( -12 / -12 =1; -5 / -12 = 5 / 12)

  Add 3 to each side

  k-3+3 = 5 / 12 +3

          k = 5+36 / 12

           k = 41 / 12

answered Jan 7, 2013 by krish Pupil

Related questions

asked Nov 4, 2014 in CALCULUS by anonymous
...